Metazoan endoparasites of Serrasalmus marginatus (Characiformes: Serrasalminae) in the Negro River, Pantanal, Brazil - Wagner Vicentin (Revista Brasileira de Parasitologia Veterinária, 2011)
In order to inventory the metazoan endoparasites ofSerrasalmus marginatus, 91 specimens were examined. Theywere captured in the Negro River in Pantanal wetland, State of Mato Grosso do Sul, Central-Western Brazil, fromOctober 2007 to August 2008. Parasites of six taxa were recovered:Procamallanus(Spirocamallanus)inopinatus,Contracaecumsp. (Nematoda), metacercarial typeDiplostomulum(Digenea),Brevimulticaecumsp. (Nematoda) andSebekia oxycephala,Subtriquetrasp. 1 andSubtriquetrasp. 2 (Pentastomida). The latter five species are reported for thefirst time inS. marginatus.